KYAI KAMPUNG, ISLAMISME, DAN KETAHANAN BUDAYA LOKAL (Pandangan Kyai Abdullah Faishol tentang Ketahanan Budaya dan Visi NU Sukoharjo) - Zainal Habib (Balai Penelitian dan Pengembangan Agama Semarang, 2018)
The presence of ideological Islamist groups in the public space of Sukoharjo ideologically threatens the existence of NU, mainstreams’ Islamic group. Kyai Abdullah Faishol is one of a religious leader in NU (kyai NU), an organic religious leader (organic kyai), who raise the structure and culture of NU to fight the movement of the Islamic group. Culture is chosen by Kyai Faishol because it has a life force that is always united and practiced in daily life by the community. Religious leaders such as Kyai Abdullah Faishol become the last cultural basis in defending amaliyah and other local wisdom from the aggression of Islamist groups. Through cultural media such as syi’iran, kyai Faishol retained the local culture of Walisongo heritage. Besides the syi’ir, Kyai Faishol also forms a cultural knot and initiates the religious cultural institutions such as yasinan assembly, assembly of dzikr and sholawat “Hubbun Nabi” for the transformation of the moderate tolerant pattern of religiosity.